DMC in EFL classroom: Its possible pedagogical values to develop students’ digital literacy and creative expression - Raynesa Noor Emiliasari; Emi Emilia; Budi Hermawan (TLEMC (Teaching and Learning English in Multicultural Contexts), 2025)
This study investigates the implementation of Digital Multimodal Composing (DMC) in an Indonesian EFL context, with particular attention to students’ composing processes and their application of the Grammar of Visual Design (GVD). Adopting a qualitative case study design, the study was conducted over one academic semester and integrated the Genre-Based Approach (GBA) with multimodal instruction. The participants were twenty-eight undergraduate students enrolled in an English Education program who worked in four groups to produce four digital posters as the final outcome of the Independent Construction stage. All posters were designed using the Canva application and represented different genres, including narrative, informative, and persuasive texts. Data were collected through classroom video recordings, field notes, and semi-structured interviews with six purposively selected students. The findings show that students were able to integrate visual, verbal, and spatial modes in their poster designs, demonstrating an emerging understanding of representational, interactional, and compositional meanings. While students initially experienced difficulties in balancing modes and making deliberate design choices, scaffolded instruction through the GBA stages supported their gradual development of multimodal awareness. The posters illustrate students’ ability to apply GVD principles in culturally relevant and socially meaningful contexts, highlighting the pedagogical value of DMC for fostering digital literacy, creative expression, and genre awareness in EFL learning.Keywords: Digital Literacy, DMC, EFL Classroom, GBA